The Influence of Zero‐Profile Implant Selection on the Outcomes of Anterior Cervical Discectomy and Fusion - Xing‐Jin Wang; Jun‐Bo He; Ting‐Kui Wu; Bei‐Yu Wang; Xin Rong; Quan Gong; Hao Liu (Orthopaedic Surgery)
ABSTRACT Objectives Anterior cervical discectomy and fusion (ACDF) has been widely used in the treatment of cervical degenerative disc disease (CDDD). Previous studies have demonstrated that the size of implants in ACDF determines radiological and clinical outcomes. However, the principles of choosing an appropriate implant size in ACDF remain controversial. The study aimed to elucidate the influence of the cage size of Zero‐profile implant system and offer proposals on the selection of implant size during ACDF. Methods This retrospective study analyzed 109 patients who underwent single‐level ACDF from March 2011 to April 2020 with the Zero‐profile implant system. The patients were categorized into two groups based on the preoperative mean height of adjacent segments (Hm). Clinical outcomes included the Japanese Orthopaedic Association scores (JOA), Neck Disability Index (NDI) and visual analog scale (VAS). In addition, radiographical analysis encompassed cervical lordosis (CL), functional spinal unit (FSU) angle, range of motion (ROM) of the total cervical spine and the FSU, anterior and posterior FSU height, C1–C7 sagittal vertical axis (SVA), C2–C7 SVA, the center of gravity of the head (CGH)‐C7 SVA as well as T1 slope (T1S) measurements. Besides, bone fusion rates, anterior bone loss, subsidence, and adjacent segment degeneration were also recorded. Results Overall, 37 patients in Group A had an implant size ≥ Hm while 72 patients in Group B had an implant size < Hm. The preoperative general data and radiological parameters were comparable between the groups. At the last follow‐up, both groups had satisfactory clinical outcomes. As for radiological outcomes, the anterior and posterior FSU heights were significantly higher in Group A compared to Group B (p < 0.05) after ACDF. Besides, both groups corrected and maintained the CL and FSU. However, the average C1–C7 SVA and C2–C7 SVA at the last follow‐up were significantly higher in the Group B than in the Group A (C1–C7 SVA: 27.42 ± 9.23 mm vs. 31.76 ± 10.68 mm, p = 0.038; C2–C7 SVA: 14.65 ± 7.27 mm vs. 19.64 ± 8.68, p = 0.003). Additionally, the fusion rates were significantly higher in Group A at the first two follow‐up visits. Conclusion Our study showed that an appropriate size of Zero‐profile implant system is crucial to achieving favorable clinical and radiological outcomes after performing ACDF. Implants with a larger height but not oversize could maintain the cervical sagittal balance and FSU height and achieve early bone fusion. Therefore, a larger height might be a better choice for achieving a satisfactory long‐term prognosis if Zero‐profile implants of adjacent size both fit the disc space properly.